Cell Therapy for Stroke - Savitz, Sean I. (The American Society for Experimental NeuroTherapeutics, Inc., 2004)
Summary: Increasing experimental evidence suggests that cell transplantation can enhance recovery from stroke in animal models of focal cerebral ischemia. Clinical trials have been investigating the effects of a human immortalized neuronal cell line and porcine fetal neurons in stroke victims with persistent and stable deficits. Preclinical studies are focusing on the effects of human stem cells from various sources including brain, bone marrow, umbilical cord, and adipose tissue. This review presents an overview of preclinical and clinical studies on cell therapy for stroke. We emphasize the current, limited knowledge about the biology of implant sources and discuss special conditions in stroke that will impact the potential success of neurotransplantation in clinical trials.